A inserção do artigo 227 na Constituição Federal de 1988: os movimentos sociais, os atores políticos e a causa do menor - Maria Nilvane Fernandes; Angela Mara de Barros Lara (Ciências Sociais Unisinos)
This article analyzes, in an unprecedented way, the historical movement that inserted the paradigm of children as individuals with rights in opposition to a minorist perspective in the Federal Constitution of 1988, represented in the article 227. This process consolidated social movements that became organizations that defended children’s rights and contributed to the drafting of the Statute of the Child and Adolescent, in 1990. The study describes the political clashes in the constituent process, the counter-movements, the internal organization of the Commissions and Sub-commissions, as well as the main parties involved in writing and reporting on the text that became the article 227 in the Magna Carta. It also identifies public hearings and debaters who presented arguments for the benefit of this agenda. In the sequence, the documentary analysis highlights the movements involved in the five Popular Amendments that collected almost two million signatures, broadening the boundaries of the discussion, and expressing the dynamics of social groups. The article concludes that in the context of the insertion of article 227 into the Federal Constitution, social movements and political actors had not surpassed the term minor in the formal setting. Therefore, the period under analysis highlights a historical movement that only consolidated itself in 1990.